Spectrographic analysis of Egyptian Cairene /r/: Is it a trill or a tap?. (April 2015) - Saleh, Marwa; Hegazi, Mona; Makram, Rania; Shoeib, Rasha; Sayed, Amal; Taher, Sally
Abstract: The /r/ phoneme is variable in manner and place of articulation, and difficult to correct worldwide. Variability could exist within the same language. The objective of this study was to determine whether Egyptian Cairene /r/ was a trill or a tap and, if both forms were present, whether they were affected by word position or adjacent vowels/consonants. The information obtained was intended to improve correction of /r/ in faulty articulation. Spectrographic analysis was done for 50 Cairene subjects, who produced /r/ in different word positions in carrier phrases. Results have shown presence of both forms in the speech of every subject, but taps were more common than trills. Trills were more common in geminated /r/, in word-medial syllable final position, especially when preceded with /e/, /æ/ or /α/, and in word-medial syllable initial position, especially when preceded by non-back consonants.